Comparação de dois métodos de otimização em modelos hidrológicos do tipo chuva-vazão - Rotunno Filho, Otto Corrêa (1989)
In the use of conceptual rainfall-runoff models we frequently face difficulties in the estimation of parameters. The automatic calibration using optimization algorithms has been a valuable alternative instrument due to the efficiency in the calibration process and the quality obtained in the performance of present comparative studies of two different conceptual catchment optimization methods. The first method is based on Rosenbrock Modified and the second one is based on Rosen’s Method which is a derivative-based optimization algorithm. For the comparative analysis the conceptual catchment rainfall-runoff, named SMAP modified, and the simple least squares criterion were employed.